Influence of growth parameters on wood density of Acacia auriculiformis - Murielle Féty Tonouewa, Jesugnon Fifamè; Honoré Biaou, Samadori Sorotori; Pélagie Assede, Eméline Sêssi; Langbour, Patrick; Rodrigue Balagueman, Ogoulonou (Maderas. Ciencia y Tecnología, 2022)
Understanding the drivers of wood density variation both within a tree and between trees is important in predicting the quality of wood logs and improving this quality through adequate forestry management. This study examined the effect of the diameter growth of Acacia auriculiformis on its wood density variation. The study was conducted in the South of Benin in four plantations of Acacia auriculiformis. Near infrared spectroscopy (NIRS) method was used to predict the basic density of 225 tree wood cores of Acacia auriculiformis. A predicting model of the average tree density using the diameter as predictor was established. The relationship between wood density and tree diameter was best described by a linear mixed-effect model. The average wood density of trees increased with the diameter. The study concluded that the quality of the species logs can be improved through regular thinning and genetic selection.